Understanding Entrepreneurial Barriers Among University Students: Evidence from Malaysia’s Undergraduate Entrepreneurs - Ng Wei Chien; Gadi Dung Paul; Zhao Sheng Nan; Rong Si Dan; Song Rui Xuan; Md Zain, M. S; Muhammad Fauzie, M. F. S.; Daisy Mui Hung Kee; Anees Jane Ali (AIBPM Publisher, 2025)
Entrepreneurship among university students plays a crucial role in fostering innovation and economic development; however, many aspiring young entrepreneurs face significant barriers that limit their inclination to start a business. This study aims to identify and analyze the primary factors that hinder entrepreneurial inclination among Malaysian undergraduates. Using a quantitative approach, data were collected from 100 students through purposive sampling and analyzed using descriptive and regression analysis. The results reveal that fear of failure is the only barrier that significantly influences entrepreneurial inclination (? = 0.30, p = 0.01), while aversion to stress and hard work (? = -0.02, p = 0.10), risk aversion (? = -0.20, p = 0.19), lack of social networking (? = -0.06, p = 0.11), and lack of resources (? = 0.16, p = 0.13) show no significant effects. These findings suggest that psychological factors, particularly the perception of failure, play a more decisive role than structural constraints. The study provides theoretical contributions to behavioral models of entrepreneurship and offers practical implications for universities and policymakers to design programs that strengthen psychological resilience and entrepreneurial readiness among students.